Localization and in-Vivo Characterization of Thapsia garganica CYP76AE2 Indicates a Role in Thapsigargin Biosynthesis. Issue 1 (8th March 2017) - Andersen, Trine Bundgaard; Martinez-Swatson, Karen Agatha; Rasmussen, Silas Anselm; Boughton, Berin Alain; Jørgensen, Kirsten; Andersen-Ranberg, Johan; Nyberg, Nils; Christensen, Søren Brøgger; Simonsen, Henrik Toft
Abstract : The secretory ducts in the root of Thapsia garganica harbor the cytotoxin thapsigargin, and the cells lining these ducts express the first enzymes in the biosynthesis of thapsigargin. Abstract: The Mediterranean plant Thapsia garganica (dicot, Apiaceae), also known as deadly carrot, produces the highly toxic compound thapsigargin. This compound is a potent inhibitor of the sarcoplasmic-endoplasmic reticulum Ca 2+ -ATPase calcium pump in mammals and is of industrial importance as the active moiety of the anticancer drug mipsagargin, currently in clinical trials. Knowledge of thapsigargin in planta storage and biosynthesis has been limited. Here, we present the putative second step in thapsigargin biosynthesis, by showing that the cytochrome P450 TgCYP76AE2, transiently expressed in Nicotiana benthamiana, converts epikunzeaol into epidihydrocostunolide. Furthermore, we show that thapsigargin is likely to be stored in secretory ducts in the roots. Transcripts from TgTPS2 (epikunzeaol synthase) and TgCYP76AE2 in roots were found only in the epithelial cells lining these secretory ducts. This emphasizes the involvement of these cells in the biosynthesis of thapsigargin. This study paves the way for further studies of thapsigargin biosynthesis.